Living with parents or grandparents increases social capital and survival: 2014 General Social Survey-National Death Index. (April 2018) - Muennig, Peter; Jiao, Boshen; Singer, Elizabeth
Abstract: Introduction: After nearly a century-long trend toward single-family living arrangements, people in wealthy nations are increasingly living in multi-generational households. Multi-generational living arrangements can, in theory, increase psychological, social, and financial capital—factors associated with improvements in health and longevity. Methods: We conducted a survival analysis using the 2014 General Social Survey-National Death Index, a prospective multi-year survey. We explored whether single generational living arrangements were associated with a higher risk of mortality than multi-generational living arrangements. Results: We explored this association for different groups (e.g., the foreign-born and those with high self-reported stress in family relationships). Healthy subjects who live in two-generation households were found to have lower premature mortality (hazard ratio 0.9, 95% confidence interval = 0.82, 0.99). Otherwise, we found little evidence that living arrangements matter for the respondents' risk of premature mortality. Conclusions: Healthy people living in two-generation households have longer survival than healthy people living on their own. Highlights: Multi-generational household living arrangements have increased in the U.S. The 2014 GSSNDI was analyzed for a survival benefit in multigenerational living. Healthy subjects living in two generational households have lower premature mortality.